2014
DOI: 10.1186/s13613-014-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

When to stop septic shock resuscitation: clues from a dynamic perfusion monitoring

Abstract: BackgroundThe decision of when to stop septic shock resuscitation is a critical but yet a relatively unexplored aspect of care. This is especially relevant since the risks of over-resuscitation with fluid overload or inotropes have been highlighted in recent years. A recent guideline has proposed normalization of central venous oxygen saturation and/or lactate as therapeutic end-points, assuming that these variables are equivalent or interchangeable. However, since the physiological determinants of both are to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 40 publications
3
108
0
2
Order By: Relevance
“…In other words, isolated severe sublingual microcirculatory dysfunction appears to be an uncommon event. Additionally, persistent mild to moderate sublingual microcirculatory alterations were still observed in septic shock survivors after early normalization of perfusion-related variables such as capillary refill time, central venous oxygen saturation *Correspondence: glennguru@gmail.com and venous-arterial PCO 2 gradients [10]. These findings could question the relevance of abnormal sublingual optical images in the absence of clinical hypoperfusion.…”
Section: When Can Microcirculatory Derangements Be Considered Clinicamentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, isolated severe sublingual microcirculatory dysfunction appears to be an uncommon event. Additionally, persistent mild to moderate sublingual microcirculatory alterations were still observed in septic shock survivors after early normalization of perfusion-related variables such as capillary refill time, central venous oxygen saturation *Correspondence: glennguru@gmail.com and venous-arterial PCO 2 gradients [10]. These findings could question the relevance of abnormal sublingual optical images in the absence of clinical hypoperfusion.…”
Section: When Can Microcirculatory Derangements Be Considered Clinicamentioning
confidence: 99%
“…However, the treatment strategy is not modified, since the first major clinical responsibility is to rule out whether these abnormalities, either at the systemic or microcirculatory level, are still flow-sensitive. This is particularly relevant since risks of over-resuscitation have been repeatedly demonstrated over the last decade [10]. A multimodal analysis of macrohemodynamics, perfusion variables and eventually of microcirculatory status in the future might help in making the decision of when to stop further resuscitation in septic shock patients [10].…”
Section: Can Microcirculatory Abnormalities Be Tracked By Systemic Pementioning
confidence: 99%
See 1 more Smart Citation
“…In septic shock patients, Ait-Oufella et al [10] showed that the capillary refill time measured at 6 hours of resuscitation was related to lactate levels, organ dysfunction, and mortality. Second, early normalization of parameters of skin perfusion including the capillary refill time was associated with survival from septic shock [11] and has been suggested as an indicator to stop fluid resuscitation in septic shock [12,13]. So far, however, it remains unclear why patients with abnormal peripheral perfusion have increased morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 There may be biphasic and/or variable responses to normalization of resuscitation variables (eg, rapid initial improvement in ScvO 2 , capillary refill time, and lactate clearance may be followed by slower trends thereafter) and further delays to normalization due to confounding by impaired hepatosplanchnic hypoperfusion. 25,26 Microcirculatory capillary blood flow (ie, use of sublingual orthogonal polarization spectral imaging) is commonly found abnormal among critically ill patients. Recent observational data have shown that disturbance in sublingual microcirculatory flow failed to correlate with patient survival, possibly because of a significant dissociation observed between sublingual and intestinal microcirculatory perfusion after fluid resuscitation.…”
Section: Optimizationmentioning
confidence: 99%